2019
DOI: 10.1186/s13075-019-1818-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of autophagy and increase in apoptosis correlates with a favorable clinical outcome in patients with rheumatoid arthritis treated with anti-TNF drugs

Abstract: BackgroundAutophagy has emerged as a key mechanism in the survival and function of T and B lymphocytes, and its activation was involved in apoptosis resistance in rheumatoid arthritis (RA). To investigate whether the relationship between autophagy and apoptosis may impact the response to the therapy, we analyzed ex vivo spontaneous autophagy and apoptosis in patients with RA subjected to treatment with anti-tumor necrosis factor (TNF) drugs and in vitro the effects of TNFα and anti-TNF drugs on cell fate.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…These citrullinated proteins are known targets for ACPAs, and the level of autophagy markers is well correlated with the titer of ACPAs [100]. Such a notion is also supported by the synchronized reduction of autophagy and levels of citrullinated proteins in patients with RA upon etanercept treatment [103]. In addition, although it is still unclear whether NETosis creates pathogenic citrullination or merely redistributes an existing citrullinome, the release of citrullinated autoantigens extracellularly has been demonstrated to trigger ACPA-associated experimental arthritis [48,99,104].…”
Section: Cellular Death Pathways and Acpa Productionmentioning
confidence: 98%
“…These citrullinated proteins are known targets for ACPAs, and the level of autophagy markers is well correlated with the titer of ACPAs [100]. Such a notion is also supported by the synchronized reduction of autophagy and levels of citrullinated proteins in patients with RA upon etanercept treatment [103]. In addition, although it is still unclear whether NETosis creates pathogenic citrullination or merely redistributes an existing citrullinome, the release of citrullinated autoantigens extracellularly has been demonstrated to trigger ACPA-associated experimental arthritis [48,99,104].…”
Section: Cellular Death Pathways and Acpa Productionmentioning
confidence: 98%
“…Our results showed that the amounts of annexin-V cells were elevated in comparison with the control group, which is in agreement with the augmented cells in the sub-G1 phase ( Figure 4A ). Numerous studies have demonstrated that the alteration of the autophagy system may act as an important contributory mechanism affecting the extent of cell death induced by anticancer agents in malignant cells [ 19 , 20 , 21 ]. To investigate the contributory role of autophagy in BKM120 cytotoxicity, the effect of CQ, a well-known autophagy inhibitor, was examined as both a single agent and in combination with the PI3K inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that TNF-α activated autophagy in peripheral lymphocytes from RA patients. The treatment with drugs that block this cytokine, such as etanercept, reduced in vitro the autophagy marker LC3-II (Vomero et al, 2019). Only patients that responded to anti-TNF therapy showed a significant reduction in autophagy levels.…”
Section: Tnf-αmentioning
confidence: 99%
“…We identified the α-synuclein as a new autophagy marker in T lymphocytes (Alessandri et al, 2012;Colasanti et al, 2014). We described that not only TNFα induced autophagy in peripheral blood mononuclear cells from rheumatoid arthritis (RA) patients, but also that the balance between autophagy and apoptosis was involved in response to therapy in RA patients treated with TNF inhibitors (Vomero et al, 2019).…”
Section: Introductionmentioning
confidence: 99%